2014
DOI: 10.1021/pr500943x
|View full text |Cite
|
Sign up to set email alerts
|

Interactome Map Reveals Phospholipid Scramblase 1 as a Novel Regulator of Hepatitis B Virus X Protein

Abstract: HBV X protein plays crucial roles during viral infection and hepatocellular carcinoma (HCC) development through interaction with various host factors. Here, we mapped the interactome of HBx using a yeast two-hybrid screen. Nine human proteins were identified as novel interacting partners of HBx, one of which is phospholipid scramblase 1 (PLSCR1). PLSCR1 is an interferon-inducible protein that mediates antiviral activity against DNA and RNA viruses. However, the molecular mechanisms of PLSCR1 activity against H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…The present study also demonstrated that the expression of PLSCR1 in primary liver cancer was associated with the HBs-Ag status. Yuan et al ( 24 ) reported an important role for PLSCR1 in the host defence against HBV infection and the development of primary liver cancer in patients with HBV, which are consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The present study also demonstrated that the expression of PLSCR1 in primary liver cancer was associated with the HBs-Ag status. Yuan et al ( 24 ) reported an important role for PLSCR1 in the host defence against HBV infection and the development of primary liver cancer in patients with HBV, which are consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Among the 95 differentially expressed proteins, 16 were involved in the regulation of the host immune response (Table ). For example, IRF3, which is a key regulator of the type I IFN pathway, and phospholipid scramblase 1 (PLSCR1), which is an IFN‐inducible protein that mediates antiviral activities against DNA and RNA viruses, were expressed at significantly higher levels in PRRSV‐infected cell supernatants than mock‐infected cell supernatants. Meanwhile, the expression levels of proteins involved in the antigen processing and presentation pathways, such as MHC class II antigen, dynactin, and antigen peptide transporter 2 (TAP2), were altered by PRRSV infection.…”
Section: Resultsmentioning
confidence: 99%
“…The up‐regulated proteins in the supernatant of PRRSV‐infected PAMs were enriched mainly in the KEGG terms of the TLR signaling pathway, RIG‐I‐like receptor signaling pathway, and NF‐kappa B signaling pathway, suggesting that these secreted proteins might be involved in regulation of these signaling pathways during PRRSV infection. For example, some IFN‐stimulated proteins, such as PLSCR1, which mediates antiviral activity against DNA and RNA viruses, and IRF3, which is a key regulator of the type I IFN pathway, showed significantly higher expression levels in PRRSV‐infected cell supernatants than in mock‐infected cell supernatants. However, PRRSV has evolved various mechanisms to antagonize the type I IFN response.…”
Section: Discussionmentioning
confidence: 99%
“…This approach therefore holds promise for constructing Ad-based vectors with reduced inflammatory responses and cell loss, potentially allowing prolonged expression of therapeutic genes in preclinical and clinical gene therapy trials (Castro et al, 2014; Soria et al, 2010; Tobias et al, 2013; Wold and Toth, 2013). In vitro studies indicate that PLSCR1 may also play important roles in the antiviral response to other viruses, including herpes simplex virus (Talukder et al, 2012), vesicular stomatitis virus (Dong et al, 2004), and hepatitis B and C viruses (Metz et al, 2012; Yuan et al, 2015). Beyond virus infection, PLSCR1 may be of importance in bacterial infection (Goth and Stephens, 2001; Lu et al, 2007), autoimmune disease (Amengual et al, 2013; Bernales et al, 2008; Suzuki et al, 2010), or cancer development (Fan et al, 2012; Kodigepalli et al, 2013; Kuo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%